Dichloroacetate ameliorates myocardial ischemia-reperfusion injury via regulating autophagy and glucose homeostasis - Shuo Li; Boqia Xie; Wenqian Zhang; Tong Li (Archives of Medical Science, 2019)
Introduction Autophagy occurs in response to myocardial ischemia-reperfusion (I/R) injury and plays both a protective and detrimental role in this pathological process. Dichloroacetate (DCA) has a protective role during myocardial I/R injury, but its effects on autophagy induction are less well understood. We established a rat myocardial I/R injury model and investigated the effects of DCA on autophagy induction.